ANALISIS PENDAPATAN USAHATANI PADI SAWAH TERKENA DAMPAK PERTAMBANGAN NIKEL DI KABUPATEN KONAWE SELATAN - Hasriati, Hasriati; Tinaprilla, Netti; Suprehatin, Suprehatin (Jurnal AGRISEP, 2019)
This study aimed to analyze the income of wetland paddy farming on the affected land and not affected by nickel in the South Konawe Discrit . This study was conducted from May to July 2017. The data collected were primary data obtained from direct interviews with affected wetland farmers and not affected nickel mining, with the number of respondents as many as 100 farmers. Data were analyzed using farm income analysis. The results showed that the income of rice field farming exposed and not affected by nickel mining is significantly different. Total revenues of rice field farms affected by mining nickel mining amounted to Rp7 838 617 with a     R/C of 0.9 and total revenues of Rp -213 290.4. Meanwhile, the acceptance of paddy field farming is not affected by nickel mining which is Rp17 220 630.3 with R/C value of 1.9 and revenues at total cost Rp 6 897 157.4.